Graft nephrectomy: The SGPGI experience - Nand Kishore Arvind; Aneesh Srivastava; Anant Kumar; Subodh K Das (Indian Journal of Urology, 2002)
Background: Graft nephrectomy is often considered a hazardous procedure with high morbidity and occasional mortality, and this may pose a technical challenge. The aim of this study was to evaluate the indications, etiology and complications following graft nephrectomy. Materials and Methods: From 1988 to 2001, among total of 1,019 live related renal transplants carried at our center, 46 underwent graft nephrectomy. Patients were divided into 2 groups depending on timing of graft re-moval. The early group included 27 patients (within 2 months of transplantation) while in late group (graft re-moval after 2 months of transplantation) there were 19 patients. The 2 groups were compared in terms of indica-tion, etiology and complications. Results: In early group the indications for graft removal were acute rejection, thrombosis/infarction and hyper-acute rejection, while in late group the indications were pain, hematuria, fever, hypertension and infection along with chronic failure. Overall, the external iliac artery in-jury occurred in I and 4 patients in early and late group respectively. Major blood loss occurred in I and 6 pa-tients in early and late graft removal respectively. There were 2 deaths in early group due to ftdminant pneumoni-tis that progressed to sepsis and disseminated intravascu-lar coagulation. There were 9 major wound infections all in early group except in 2 patients of late group. Respira-tory infections occurred in 14 patients in early group and 1 in late group. In early group patients had CNS compli-cations in form of seizures, clinical depression and delusional psychosis in 12 patients. Conclusions: Our experience highlights the risk in-volved in graft nephrectomies. Severe acute rejection and thrombosis lead to early graft nephrectomies. Pain, hematuria, infection and hypertension in setting of chronic rejection are predominant causes for the delayed graft ne- phrectomies. Early graft nephrectomy, though technically easy, is associated with systemic complications; late graft nephrectomy is technically more demanding with relatively increased risk of vascular and visceral injuries.